化膿性顎下リンパ節炎を契機に診断された乳児自己免疫性好中球減少症の1例 - 谷口, 佳孝; 小原, 浩; 西尾, 順太郎; 平野, 吉子; 並川, 麻理 (日本口腔外科学会雑誌, 2009)
We report the case of a 9-month-old girl with autoimmune neutropenia in whom pyogenic submandibular lymphadenitis was diagnosed. She visited our hospital for evaluation and treatment of swelling of the left submandibular region, unaccompanied by fever. Hematological examination showed a neutrophil count of 178 cells/μl, indicating severe neutropenia. A CT scan showed abscess formation in the left submandibular region. We performed surgical drainage under general anesthesia. Culture of the drainage fluid revealed methicillin-resistant Staphylococcus aureus. Antibiotics were administered, and the swelling of the submandibular region disappeared. Immunological examination of the serum was positive for neutrophil-binding IgG. This finding suggested that the neutropenia was caused by autoantibodies against neutrophils. Although the neutrophil count increased transiently after treatment with granulocyte colony-stimulating factor for 6 days, neutropenia recurred. Trimethoprim-sulfamethoxazole was given orally every other day for infection prophylaxis. Recurrence of infectious disease, including cervical lymphadenitis, has not occurred up to the present.